Entrepreneur Hubris, Organizational Ambidexterity, and Dynamic Capability Construction - Guo, Yan; Huang, Pei-Wen; Ciu, Chu; Fang, Shih-Chieh; Tsai, Fu-Sheng (Frontiers in Psychology, 2022)
This paper demonstrated the influences of initiation, development, turn-down, and reinitiation of the dynamic capability of an entrepreneurial firm in the solar energy industry. The focus is on the impact of entrepreneurial hubris, which may affect the decision of ambidexterity that can vitalize dynamic capability. The findings indicate that, when the major decision maker (the founder entrepreneur) has the trait of hubris, the decision-making process may be overly arbitrary, and a decision of being exploratory or exploitative alone is likely to be made. On the contrary, when the founder entrepreneur is aware of the hubris and shares decisive power, the decision of being ambidextrous as a dynamic capability is more freely achieved. This paper contributes by discovery of the cognitive-based microfoundation of entrepreneurial ventures and linkage of such microfoundation to organizational ambidexterity.